Strategies and attitudes of teachers towards learners with behaviour problems in rural areas of the Limpopo Privince, South Africa - Mudau, Mpheletshedzeni Joyce (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEd)--Stellenbosch University, 2002.